Contribution of Physical Fitness, Cerebrovascular Reserve and Cognitive Stimulation to Cognitive Function in Post-Menopausal Women - Eskes, Gail A.; Longman, Stewart; Brown, Allison D.; McMorris, Carly A.; Langdon, Kristopher D.; Hogan, David B.; Poulin, Marc (Frontiers in Aging Neuroscience, 2010)
Studies of the effects of physical fitness on cognition suggest that exercise can improve cognitive abilities in healthy older adults, as well as delay the onset of age-related cognitive decline. The mechanisms for the positive benefit of exercise and how these effects interact with other variables known to influence cognitive function (e.g., involvement in cognitive activities) are less well understood. The current study examined the associations between the physical fitness, cerebrovascular blood flow regulation and involvement in cognitive activities with neuropsychological function in healthy postmenopausal women. Methods: Forty-two healthy women between the ages of 55 and 90 were recruited. Physical fitness (V˙ o2max), cerebrovascular reserve (cerebral blood flow during rest and response to an increase in end-tidal (i.e., arterial) PCO2), and cognitive activity (self-reported number and hours of involvement in cognitive activities) were assessed. The association of these variables with neuropsychological performance was examined through linear regression. Results: Physical fitness, cerebrovascular reserve and total number of cognitive activities (but not total hours) were independent predictors of cognitive function, particularly measures of overall cognitive performance, attention and executive function. In addition, prediction of neuropsychological performance was better with multiple variables than each alone. Conclusions: Cognitive function in older adults is associated with multiple factors, including physical fitness, cerebrovascular health and cognitive stimulation. Interestingly, cognitive stimulation effects appear related more to the diversity of activities, rather than the duration of activity. Further examination of these relationships is ongoing in a prospective cohort study.